Stereoselective Synthesis of Spiro-α-methylene-γ-lactams via Chiral Quaternary 3-Aminooxindole Adducts Accessed by Zn-Mediated Allylation of Sulfinyl Ketimines - Rao, V. U. Bhaskara; Singh, Shashank; Tripathi, Krishna N.; Singh, Ravi P. (Synthesis, 2020)
An efficient method for the stereoselective synthesis of α-methylene-γ-lactams via quaternary 3-aminooxindoles with very high selectivity (up to 98% ee) is described. The methodology leads to the construction of sterically congested chiral quaternary 3-aminooxindole adducts in good yield and with moderate to excellent diastereoselectivity (dr up to 95:5). The relative stereochemistry of the chiral quaternary 3-aminooxindoles adduct and the spiro-α-methylene-γ-lactam was confirmed to be syn by single-crystal X-ray structure analysis. Furthermore, the α-methylene-γ-lactam was successfully transformed into a range of chiral synthons.
Keywords: asymmetric; allylation; sulfinyl ketimines; isatin; spiro-γ-lactams